A single blind controlled study comparing bipolar elecrocautery tonsillectomy to cold dissection method in pediatric age groups (Health Renaissance, 2014)
Background: Tonsillectomy is one of the most commonly performed operations in otolaryngology. There are many proven methods of tonsillectomy, including cold dissection and bipolar electrocautery. Objective: To compare bipolar elecrocautery tonsillectomy with cold dissection method in pediatric age groups. Methods: Single blind controlled study to compare bipolar technique against the conventional dissection/snare technique. Results: The average amount of bleeding on electrocautery side was 4.07ml and on the cold dissection side was 14.58 ml. The mean time of operation for electrocautery and cold dissection was 12.04 and 16.57 minutes respectively. On the second post operative day, 35% of the patients complained of pain on the cauterized side, 30% complained of more pain on the dissection side while 35 % experienced equal pain on both sides. Post-operative complication such as hemorrhage was not seen in both the techniques employed. Conclusion: In the present study, bipolar diathermy tonsillectomy had advantages in having less post-operative time and blood loss intraoperatively but patients experience slightly more pain than cold dissection. DOI: http://dx.doi.org/10.3126/hren.v11i3.9651 Health Renaissance 2013;11(3):270-272